Synthesis of Some 3,10-Disubstituted-6,13-dichloro bis[s-triazolo (3,4-b)-1,3,4-thiadiazino-(5,6-b:5´,6´-e)-cyclohexa-1,4-diene]derivatives as Potential Bactericides - YADAV, A.K.; SINGH, SHOBHA; RAJ, DHRUV; SINGH, VANDANA; ASTHANA, R.K.; SINGH, D. (Asian Journal of Chemistry, 2010)
Reaction of hydrzine hydrate and CS2 gives thiocarbohydrazide (1) which reacts with different aromatic acids in ethanol to give 3-substituted-4-amino-5-mercapto-striazoles (2). The condensation of 2 with chloranil in presence of anhydrous sodium acetate and absolute alcohol lead to the formation of 3,10-disubstituted-6,13-dichloro-bis[striazolo-(3,4-b)-1,3,4 thiadiazino-(5,6-b:5´,6´-e)-cyclohexa-1,4-diene]derivatives (3). The antibacterial activity of title compounds have been evaluated against S. aureus and E. coli.